2013
DOI: 10.1158/1535-7163.mct-12-0335
|View full text |Cite
|
Sign up to set email alerts
|

COX-2 and PPAR-γ Confer Cannabidiol-Induced Apoptosis of Human Lung Cancer Cells

Abstract: The antitumorigenic mechanism of cannabidiol is still controversial. This study investigates the role of COX-2 and PPAR-g in cannabidiol's proapoptotic and tumor-regressive action. In lung cancer cell lines (A549, H460) and primary cells from a patient with lung cancer, cannabidiol elicited decreased viability associated with apoptosis. Apoptotic cell death by cannabidiol was suppressed by NS-398 (COX-2 inhibitor), GW9662 (PPAR-g antagonist), and siRNA targeting COX-2 and PPAR-g. Cannabidiol-induced apoptosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
154
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 182 publications
(158 citation statements)
references
References 46 publications
2
154
0
2
Order By: Relevance
“…Here, the protective effects of CBD in an Aβ-induced neuroinflammatory mouse model were abolished by a PPARγ antagonist, but no evidence was given as to whether this was a direct or indirect effect [198]. CBD can also positively modulate COX via increased mRNA and protein expression of PPARγ and COX2, which also suggests that a COX2-generated increase in PGD 2 and 15d-PGJ 2 could underlie PPARγ activation in addition to any direct activation of PPARγ by CBD [18,54,93]. A possible mechanism for this is suggested by the observation that NRF2 can increase PPARγ expression as CBD can activate NRF2 [79,199,200].…”
Section: Cbd Receptor Targets In Neurodegenerationmentioning
confidence: 91%
See 4 more Smart Citations
“…Here, the protective effects of CBD in an Aβ-induced neuroinflammatory mouse model were abolished by a PPARγ antagonist, but no evidence was given as to whether this was a direct or indirect effect [198]. CBD can also positively modulate COX via increased mRNA and protein expression of PPARγ and COX2, which also suggests that a COX2-generated increase in PGD 2 and 15d-PGJ 2 could underlie PPARγ activation in addition to any direct activation of PPARγ by CBD [18,54,93]. A possible mechanism for this is suggested by the observation that NRF2 can increase PPARγ expression as CBD can activate NRF2 [79,199,200].…”
Section: Cbd Receptor Targets In Neurodegenerationmentioning
confidence: 91%
“…Conversely, a different study showed that 318 μM CBD had no effect upon the in vitro activities of COX1 and COX2 (Table 2) [69], while in vivo administration of CBD had no effect upon COX2 activity in tumor tissue [68] (Table 2). However, a further study suggested that CBD may modulate COX2 activity by stimulating transcription and/or translation in some subtypes of cells [18]. While the concentrations described above are unlikely to be physiologically achievable, a more recent study suggested that 10 μM CBD increased arterial vasorelaxation in diabetic Zucker rats, which was associated with COX1 and COX2 stimulation via an allosteric mechanism [93].…”
Section: Cyclooxygenases and Lipoxygenasesmentioning
confidence: 97%
See 3 more Smart Citations